Perancangan dan Pengembangan Prothese Kaki Bagian Bawah Lutut dengan Menggunakan Quality Function Deployment - Damayanti, Retno Wulan; Susmartini, Susy; Herdiman, Lobes (Performa: Media Ilmiah Teknik Industri, 2003)
This paper proposes design and development of below knee prosthesis using quality function deployment (QFD) to return the balance of human body so the patient can do their daily activities. In this method, design and development based on the voice of customer. The result of design and development is below knee prosthesis using insert silicone socket, cuff rubber suspension system, adaptor rotator ankle, jaipur foot and stainless steel pylon as strengteness. It is hope, that this below knee prosthesis be able to accommodate the user’s need and want.